Women in patriarchal society - Sarker, Profulla Chandra (New Delhi, India : Serials Publications, 2010)
With special reference to India and Bangladesh; contributed articles.
Includes bibliographical references and index.
BIED
Keywords: Women in development -- India; Women in development -- Bangladesh; Women -- India -- Social conditions; Women -- Bangladesh -- Social conditions; Patriarchy -- India; Patriarchy -- Bangladesh; Women -- Social conditions